The Role of Elderly Health Tests as Early Prevention of Chronic Diseases During the Covid-19 Pandemic in the Region of Medan Sunggal District - Elfira, Eqlima; Girsang, Bina Melvia; Nurbaiti; Sitohang, Ance Marintan D.; Faswita, Wirda (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
A health test is an examination carried out to determine a person's health standards. Priority checks are carried out on the elderly, where the elderly may experience health problemsHealth Checkup includes checking blood pressure, blood glucose, urine and cholesterol. The objective of this activity is to carry out early detection of the elderly to prevent chronic diseases. The activity was carried out on August 12, 2021 in the area of the Medan Sunggal sub-district. The examination gave positive results for the community. People who check him can know the condition of his body. This examination also provides input and recommendations for therapy that must be carried out by the elderly while health is still available. This condition is marked by a change in the value of the Health examination results which increases from the normal amount.